2018
DOI: 10.30835/2413-7510.2018.134357
|View full text |Cite
|
Sign up to set email alerts
|

Content and biological value of protein in grain of spring barley accessions

Abstract: In 2015-2017, the Plant Production Institute named after V.Ya. Yuriev of NAAS studied the dependence of protein content on growing conditions and genotype and evaluated its biological value for food production. Seventy barley lines and cultivars belonging to different varieties and originating from different eco-geographical regions were the test material. It was established that under the similar weather conditions of 2015-2017 the protein content in grain of spring barley accessions insignificantly depended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…Protein digestibility is important. We showed that cultivars Parnas and Berkut had highly digestible protein: 69.80-74.20 mg of tyrosine per 1 gram of protein compared to 53.90 mg/g in wheat (Table 4) [25]. Thus, cultivars Parnas and Omskiy Golozyornyy 1 are sources of high protein digestibility by proteolytic enzymes.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Protein digestibility is important. We showed that cultivars Parnas and Berkut had highly digestible protein: 69.80-74.20 mg of tyrosine per 1 gram of protein compared to 53.90 mg/g in wheat (Table 4) [25]. Thus, cultivars Parnas and Omskiy Golozyornyy 1 are sources of high protein digestibility by proteolytic enzymes.…”
mentioning
confidence: 77%
“…We studied starting material and bred new spring food barley cultivars. In order to provide dietic and baby foods, a breeding program was implemented to cross domestic cultivars, which are well-adapted to the conditions of Eastern Ukraine and resistant to lodging and diseases, with waxy naked accessions [25].…”
mentioning
confidence: 99%
“…зразків у дослідженнях. Зокрема, можна відзначити дещо нижчі показники вмісту білка у зерні шестирядкових ячменів (Lim = 12,6-14,9%) порівняно з дворядковими (Lim = 13,1-17,0%) та голозерними (lim = 13,8-15,9%), що відзначали й інші дослідники [26]. Якщо застосувати статистичні величини для порівняння, то за середнім вмістом білка в зерні плівчасті зразки (х = 15,2%) переважали голозерні (х = 14,6%), а модальний показник і медіана відповідали середньому значенню у вибірках.…”
Section: таблиця 1 гідротермічні умови 2020-2022 рр у період вегетаці...unclassified